Ad-hoc, mobile, and wireless network : 15th International Conference, ADHOC-NOW 2016, Lille, France, July 4-6, 2016 : proceedings /: 15th International Conference, ADHOC-NOW 2016, Lille, France, July 4-6, 2016 : proceedings. (2016) - Unknown
No abstract available